The Spectacular City : Violence and Performance in Urban Bolivia - Goldstein, Daniel M., 1965- (Book collections on Project MUSE., 2004)
This study analyzes a popular festival and vigilante lynching, examining them as a form of political spectacle performed by improverished people who want to gain access to the potential benefits of citizenship in a modern city.